Child maltreatment and management of pediatric patients during COVID-19 pandemic: Knowledge, awareness, and attitudes among students of medicine and surgery. A survey-based analysis - Aulino, Giovanni; Beccia, Flavia; Rega, Michele; Siodambro, Chiara; Capece, Giuseppe; Boccia, Stefania; Lanzone, Antonio; Oliva, Antonio (Frontiers in Public Health, 2022)
Purpose of the study To assess perception, awareness, and attitudes regarding the medico-legal relevance of child maltreatment and management of pediatric patients during the COVID-19 pandemic in a cohort of medicine and surgery students, with a particular focus on child safety and maltreatment. Methods A cross-sectional, web-based survey was conducted through an anonymous questionnaire on the personal websites of Università Cattolica del Sacro Cuore medical students. Results The study included 1,166 participants, the majority of whom were experienced with child maltreatment and defensive medicine; only a small percentage was aware of the government's efforts to prevent child maltreatment and safeguard vaccination physicians. Moreover, there was no agreement on the use of telemedicine for non-serious pediatric patients or on the consequences it might have on their health. Finally, the detrimental impacts of lockdown on children's mental health are a major worry. Conclusions Knowledge of these themes is mainly implemented by deepening these concepts during the undergraduate studies since a high level of knowledge on child maltreatment and on the management of COVID-19 pandemic was significantly associated with clinical years of course. Specific seminars analyzing telemedicine and legislative protections concerning minors and those concerning vaccination doctors should be included in the study plan to raise awareness these concepts.